A novel digital information service for federating distributed digital entities. (January 2016) - Mustacoglu, Ahmet F.; Fox, Geoffrey C.
Abstract: We investigate the performance and the scalability metrics of a Digital Information Service framework that is used for unifying and federating online digital entities by retrieving and managing information located on the web. The Digital Information Service consists of tools and web services for supporting Cyberinfrastructure based scientific research. This system supports a number of existing online Web 2.0 research tools (social bookmarking, academic search, scientific databases, journal and conference content management systems) and aims to develop added-value community building tools that leverage the management and federation of digital entities and their metadata obtained from multiple services. We introduce a prototype implementation and present its evaluation. As the results indicate, the proposed system achieves federation and unification of digital entities coming from different sources with negligible processing overheads. Highlights: Performance and scalability metrics of the Digital Information Service framework. We unified and federated online digital entities located on the web. Our proposed system retrieves and manages information located on the web. This system supports a number of existing online Web2.0 research tools. Social bookmarking, academic search, journal-conference content management systems. We introduce a prototype implementation and present its evaluation. The proposed system achieves federation and unification of digital entities.